2018
DOI: 10.1371/journal.pone.0205735
|View full text |Cite
|
Sign up to set email alerts
|

The expected labor progression after labor augmentation with oxytocin: A retrospective cohort study

Abstract: ObjectiveTo describe labor progression patterns with oxytocin for augmentation in women who achieve vaginal delivery; and to determine how long one should wait with effective uterine contraction before labor arrest can be diagnosed.DesignPopulation-based retrospective cohort study.PopulationThe final sample involved 8,988 women with singleton gestation, term live birth, vertex presentation, no previous cesarean section, vaginal delivery, and neonatal Apgar score at 5 minutes at 7 or higher, and complete inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Several studies have compared the results of high and low-dose oxytocin administration regimens [15,23]. Still, few have focused on the duration of the oxytocin infusion and total amount administrated, dose-escalation and intervals and outcomes for women and babies [24][25][26][27]. Studying these aspects is particularly crucial in the light of the latest reports on the longer than the previously believed half-life of oxytocin that can lead to high accumulation and unnecessary exposure in women and children [28].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have compared the results of high and low-dose oxytocin administration regimens [15,23]. Still, few have focused on the duration of the oxytocin infusion and total amount administrated, dose-escalation and intervals and outcomes for women and babies [24][25][26][27]. Studying these aspects is particularly crucial in the light of the latest reports on the longer than the previously believed half-life of oxytocin that can lead to high accumulation and unnecessary exposure in women and children [28].…”
Section: Introductionmentioning
confidence: 99%
“…The results also reminded us that routine monitoring of uterine contractions after ureteroscopy might help to avoid pregnancy complications. Compared with primipara, the cervix of multipara is easier to expand, which means a sooner labor process [21,22]. Literature has shown that uterine contraction was stronger for multipara during labor and more analgesics were needed for painless delivery [23].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with primipara, the cervix of multipara is easier to expand, which means a sooner labor process [21,22] . Uterine contraction is stronger for multipara during labor and more analgesics are needed for painless delivery [23] .…”
Section: Discussionmentioning
confidence: 99%